Prevalence and Risk Factors for Depression among Parents of Children Born Preterm: A Systematic Review and Meta-analysis of The Evidence Since 2000 - Moorhouse, Megan A. M.; Jeyagaran, Piranavi; Okoli, George N.; Bolton, James M.; Askin, Nicole; Cheung, Kristene; Lix, Lisa M.; Garland, Allan; Louis, Deepak (American Journal of Perinatology, 2025)
Previous reviews of depression among parents of preterm children were restricted to mothers within the first year of preterm delivery. We aimed to systematically review the prevalence and risk factors for depressive symptoms among mothers and fathers in the first 5 years following preterm birth.This systematic review was undertaken following the Cochrane Handbook for Systematic Reviews of Interventions Guidelines and reported using the preferred reporting items for systematic reviews and meta-analysis guidelines. Peer-reviewed, all-language, observational studies from the year 2000 that assessed the prevalence and/or risk factors for depression among parents of children born preterm (<37 weeks gestation) in the first 5 years following preterm birth, using validated clinical scales, were included. Medline, Embase, Web of Science Core Collection, CINAHL, PsycINFO, and Cochrane Central were searched on July 29, 2021. The NIH quality assessment tool was used. Meta-analysis was performed using inverse variance effects models to estimate prevalence and identify risk factors.Seventy-eight studies were included. The majority were English language (n = 71), European (n = 32), and cross-sectional studies (n = 44), using the EPDS scale (n = 45). The prevalence of depressive symptoms among mothers was 25% (95% confidence interval (CI): 21–31%; n = 72) in the first year, and 20% (13–30%; n = 8) in the second to fifth year, while for fathers, the rates were 13% (8–22%; n = 15) and 11% (2–50%; n = 1), respectively. Eastern Mediterranean region had the highest prevalence of maternal depressive symptoms in the first year (48% [25–72%; n = 3]), while it was the Western Pacific region for fathers (17% [15–19%]). Low educational status (odds ratio: 3.5; [95% CI: 1.9–6.5; n = 2]) was associated with depressive symptoms among mothers in the first year.Mothers and fathers had a high prevalence of depressive symptoms in the first 5 years following preterm birth, with region variations in the prevalence (PROSPERO registration no.: CRD42021260748).
Keywords: prematurity; depression; mothers; fathers